Traditional Chinese Medicine of Angelicae Pubescentis Radix: A Review of Phytochemistry, Pharmacology and Pharmacokinetics - Lu, Yaqi; Wu, Hongwei; Yu, Xiankuo; Zhang, Xiao; Luo, Hanyan; Tang, Liying; Wang, Zhuju (Frontiers in Pharmacology, 2020)
Angelicae Pubescentis Radix (APR) is a widely used antirheumatic Chinese medicinal herb known as “Duhuo” in China. It has the effects of dispelling wind and removing dampness, diffusing impediment, and relieving pain, and is mainly indicated for rheumatic arthritis with pain in the lower back and knees, and headache. To the best of our knowledge, an attempt is made to provide an up-to-date review on these aspects based on published materials, including ancient and modern books; Master's and doctoral theses; monographs on medicinal plants; the pharmacopoeia of different countries, websites for publication of patent and electronic databases, such as SCI finder, PubMed, Web of Science, ACS, Science Direct, Wiley, Springer, Taylor, CNKI, and Google Scholar. APR, which has a good clinical effect, has been used for traditional Chinese medicine more than 2000 years. Since 1957, a variety of chemical constituents have been reported from the medicinal plants of this herb, mostly coumarins and volatile oil. In the past 30 years, numerous studies have shown that the extracts and compounds isolated from APR showed effective analgesic and anti-inflammatory actions, also showing well effects on central nervous system, effects on cardiovascular system and deworming activity. In addition, we also present and discuss the botany, traditional medicinal use, pharmacokinetics, toxicity, quality control, future trends and prospects of APR. All this information suggest that future research of APR should be supplemented in the area of pharmacology and toxicology to provide further insight on the clinical use and quality control.